2022
DOI: 10.1007/s00122-022-04171-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping identifies common bunt (Tilletia caries) resistance loci in bread wheat (Triticum aestivum) accessions of the USDA National Small Grains Collection

Abstract: Key message Association mapping and phenotypic analysis of a diversity panel of 238 bread wheat accessions highlights differences in resistance against common vs. dwarf bunt and identifies genotypes valuable for bi-parental crosses. Abstract Common bunt caused by Tilletia caries and T. laevis was successfully controlled by seed dressings with systemic fungicides for decades, but has become a renewed threat to wheat yield and quality in organic agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Chromosome 2B harbors the Bt1 gene that provides resistance against several T. caries and T. laevis isolates (Goates, 2012; Sears et al., 1960), but we are not sure of the exact physical position of this gene. Minor to moderate effect Cbt resistance QTLs have also been reported in wheat on chromosome 2B by different authors, including at 811 Mb near BS00012463_51 in the Canadian spring wheat diversity panel (Iqbal et al., 2022), 581 Mb near Ku_c71357_859 in a bread wheat accessions of the USDA National Small Grains Collection (Ehn et al., 2022), and 8–9 Mb in a diversity panel of both spring and winter wheat accessions (Steffan et al., 2022), but none of these QTLs are physically close to QCbt.dms‐2B identified in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Chromosome 2B harbors the Bt1 gene that provides resistance against several T. caries and T. laevis isolates (Goates, 2012; Sears et al., 1960), but we are not sure of the exact physical position of this gene. Minor to moderate effect Cbt resistance QTLs have also been reported in wheat on chromosome 2B by different authors, including at 811 Mb near BS00012463_51 in the Canadian spring wheat diversity panel (Iqbal et al., 2022), 581 Mb near Ku_c71357_859 in a bread wheat accessions of the USDA National Small Grains Collection (Ehn et al., 2022), and 8–9 Mb in a diversity panel of both spring and winter wheat accessions (Steffan et al., 2022), but none of these QTLs are physically close to QCbt.dms‐2B identified in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies reported genes ( Bt4 , Bt5 , and Bt6 ) and QTLs associated with Cbt resistance on chromosome 1B (Dumalasová et al., 2012; Ehn et al., 2022; Fofana et al., 2008; Iqbal et al., 2022; Mourad et al., 2018; Muellner et al., 2021; Scmidt et al., 1969; Singh et al., 2016; Wang et al., 2009), 2B (Chen et al., 2016; Ehn et al., 2022; Iqbal et al., 2022; Steffan et al., 2022), and 6D (Gordon et al., 2020; Iqbal et al., 2022; Singh et al., 2016). The positions of the Cbt resistance genes and QTLs on 1B varied across populations and includes 11.2 Mb near BS00032266_51 in a diversity panel of bread wheat accessions from the USDA National Small Grains Collection (Ehn et al., 2022), 4.4–38.9 Mb in two RIL populations derived from Blizzard/Rainer and Bonneville/Rainer (Muellner et al., 2021), and 645.2 Mb in Canadian spring wheat (Iqbal et al., 2022). The physical position of the QCbt.dms‐1B identified in the present study, therefore, overlapped with the QTLs reported in the USDA bread wheat accessions and the two RIL (Blizzard/Rainer and Bonneville/ Rainer) populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differential lines are available in the Department of Agricultural Research Service, National Small Grains Collection (NSGC) in Aberdeen, ID, and could be easily separated from each other, which makes them globally important [ 40 ]. They are very helpful in identifying the resistant genes as they are isolines carrying only one resistant gene [ 39 , 40 , 42 ]. Based on the results of the differential lines, Bt6 , Bt7 , Bt9 , Bt10 , Bt11 , Bt12 , Bt13 , Bt15 , and Btp are effective resistance genes to the Nebraska common bunt race.…”
Section: Discussionmentioning
confidence: 99%
“…The results of collection of samples are shown Table 2 spread of covered smut disease in wheat caused by a fungus Tilletia spp. in all areas collection sample and this is compound with what was mentioned [6] from that the disease is widespread in most planted area of wheat in most countries of the world.…”
Section: Collection Of Samplesmentioning
confidence: 92%